2017
DOI: 10.1080/10758216.2017.1289818
|View full text |Cite
|
Sign up to set email alerts
|

Which Social Media Facilitate Online Public Opinion in China?

Abstract: Why does online public opinion emerge in some social media more easily than in others? Building on research on authoritarian deliberation, we describe spaces for political discussion in Chinese cyberspace in terms of interactivity, which results in different forms of political discussion. Drawing on semi-structured qualitative expert interviews with information and communications technology professionals at Tencent, Weibo, and Baidu, we explain how major social media differ in terms of their structure and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 30 publications
(33 reference statements)
0
24
0
1
Order By: Relevance
“…Previous studies on the democratic potential of social media in China have focused on two competing views, one of which stresses the democratizing effect of social media (Cairns & Carlson, 2016), and the other emphasizes the quick adaptation of the CCP to the social media environment and its efforts to use the new media to its own advantage (Hyun et al, 2014;Hyun & Kim, 2015). However, recent studies have demonstrated that the political information available on Weibo is more diverse than that on traditional state-led mass media (Rauchfleisch & Sch€ afer, 2015;Stockmann & Luo, 2017) and that Chinese citizens can still read grievances and critical opinions on Weibo (Qin et al, 2017). Arguably, because those posts are useful in monitoring public opinion and enhancing the accountability of local governments and politicians, the central government allows people to post critical comments on political issues despite its massive censorship and manipulation (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies on the democratic potential of social media in China have focused on two competing views, one of which stresses the democratizing effect of social media (Cairns & Carlson, 2016), and the other emphasizes the quick adaptation of the CCP to the social media environment and its efforts to use the new media to its own advantage (Hyun et al, 2014;Hyun & Kim, 2015). However, recent studies have demonstrated that the political information available on Weibo is more diverse than that on traditional state-led mass media (Rauchfleisch & Sch€ afer, 2015;Stockmann & Luo, 2017) and that Chinese citizens can still read grievances and critical opinions on Weibo (Qin et al, 2017). Arguably, because those posts are useful in monitoring public opinion and enhancing the accountability of local governments and politicians, the central government allows people to post critical comments on political issues despite its massive censorship and manipulation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although this effect was not fully supported in the social media sample, it suggests that the political implications of WeChat use are remarkably different from those of Weibo. Although WeChat provides an online social networking service like that of Weibo, its technological features strongly facilitate social interactions among people who know each other in person, which limits the dissemination of public information beyond intimate social circles (Stockmann & Luo, 2017). Furthermore, WeChat emerged shortly before Xi's administration started to tighten regulations on the media industry (Creemers, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to He (2006) "Chinese authoritarian deliberation is authoritarian in the sense that top leaders are not elected; therefore, deliberation takes place under oneparty domination" (p. 134). Indeed, over the past few decades the Chinese government has experimented with and established numerous democratic institutions designed to provide feedback and information from its citizenry in promotion of state policy (Fishkin, He, Luskin, & Siu, 2010;He, 2006He, , 2014He & Warren, 2011;Jiang, 2008;Stockmann & Luo, 2017). This feedback system, and notion of authoritarian deliberation, operates on a "system of modern science and technologies, and must appeal to reason rather than force" (He, 2006, p. 135).…”
Section: Case Study One: Authoritarian Technique In Chinamentioning
confidence: 99%